UI/UX Design of a Website Based Application for Rice Harvest Collectors in Kotanegara Village Design Thinking Method - Wahyu Kurniawan; Apriansyah; Jimmie (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
Kotanegara Village is located in East Ogan Komering Ulu (OKU) Regency, South Sumatra, and the majority of its residents make a living as farmers, especially rice. This village has abundant natural potential, but faces challenges in accessibility, infrastructure, and fluctuations in the price of agricultural products. Village communities implement a culture of mutual cooperation and still depend on the agricultural sector for their livelihood. problems faced by farmers in Kotanegara Village in promoting rice crops, especially due to the lack of access to effective promotional media. Most farmers still use conventional methods. The researcher aims to create a Website-Based UI/UX Application Design for Rice Crop Collectors in Kotanegara Village with the Design Thinking Method" aims to provide innovative solutions that focus on user needs. Through the Design Thinking method, this study succeeded in designing an application prototype designed to make it easier for collectors to manage crop yields, access market price information, and improve coordination with farmers. The results of this study show that the application of website-based technology can support work efficiency, transparency, and better data management.